Fake News Detection Using Albert-base-v2 transformer and CNN-BiLSTM architectures: A Comparative Analysis of Transformer-Based and Deep Learning Approaches - Zhang, Chi (Informatica, 2025)
The widespread propagation of fake information via social media platforms has been a source of severe concern for misinformation and its potential impact on society. This study compares the Albert-base-v2 transformer and CNN-BiLSTM models to identify fake news on the Fake News Sample-Pontes dataset. The proposed models were trained and evaluated using the Fake News Sample (Pontes) dataset from Kaggle, which includes over 45,000 news articles labeled as real or fake, based on predefined criteria. Preprocessing is done on the dataset by eliminating punctuation, removing non-English characters, and tokenization for improvement in the model's performance. Five deep learning architectures—2-CNN 2-BiLSTM, 3-CNN 1-BiLSTM, 1-CNN 3-BiLSTM, DistilBERT, and Albert-base-v2—are evaluated. The models are trained using a 75%-20%-5% data split, where an embedding size of 300 is used in CNN-BiLSTM architectures. Performance is assessed based on accuracy, precision, recall, F1-score, and AUC-ROC metrics. Among the models, Albert-base-v2 has the best performance with 90.8% accuracy and 0.908 F1-score that outperforms 2-CNN 2-BiLSTM (accuracy of 86.1%, F1-score of 0.861) and DistilBERT (85.0% accuracy, 0.850 F1-score). Statistical significance is determined using t-tests, and class-wise performance is analyzed using a confusion matrix. The results highlight the superiority of transformer-based models over conventional deep learning methods in fake news detection. In addition, limitations, ethical considerations, and future directions toward enhancing model interpretability and efficiency are discussed.